Drug Metabolism and Personalized Therapy : Official journal of the European Society of Pharmacogenomics and Personalised Therapy (Berlin ; Boston De Gruyter, 1980)
Drug Metabolism and Personalized Therapy (DMPT ) publishes the results of research and review articles in the fields of clinical and biological pharmacology, drug metabolizing enzymes, pharmacogenetics/pharmacogenomics, pharmacokinetics and drug-drug interactions. DMPT is the official journal of the European Society of Pharmacogenomics and Personalised Therapy.
Popis urobený na základe e-zdroja z webstránky vydavateľa (viewed 17. Aug 2020)
Obsahuje bibliografické odkazy.
textový dokument
Internet via World Wide Web.
Keywords: Clinical Medicine, other; Medizin, Allgemeines; Clinical Medicine, other; Medizin, Allgemeines; elektronické časopisy; časopisy